DIGITAL PLATFORM AND BUSINESS: A BIBLIOMETRIC ANALYSIS - Normilia Abd Wahid; Adibah Hussin; Asjad Mohamed; Nurul Nadia Abd Aziz (Journal of Islamic, Social, Economics and Development, 2023)
This article discusses global research trends in digital platforms and business through bibliometric studies, examining publication output and the co-occurrence of author keywords. Metadata were obtained from Scopus, which consisted of 7639 articles published between 2013 and 2023. The VOSviewer software reviewed nine clusters. The most frequently used keywords were digital platforms, social media, digital transformation and social networking (online). These clusters represented streams of digital platform research in business. This article further discusses research opportunities related to digital platforms in support of sustainable business growth in the future.